Role of Politics, Discrimination and Favouritism in Stress and Job Performance in Pakistani Public Sector (Journal of Asian Development Studies, 2025)
This study examines the effects of organizational politics, workplace discrimination, and favoritism on workplace stress and employee performance within public sector organizations in Pakistan. Data collection involved 390 employees using structured questionnaires, and the analysis utilized Partial Least Squares Structural Equation Modelling to explore the relationships. The findings indicate that elevated perceptions of organizational politics, discrimination, and favoritism significantly heighten workplace stress, leading to a detrimental impact on employee performance. The study highlights the importance of equitable, transparent, and meritocratic approaches to reduce stress and improve employee performance.